G564(P) Pre-operative screening for sickle cell disease: improving parent and carer experiences. (27th April 2015) - Iqbal, S; Wedge, E; McPhee, M; Chua, E
Abstract : Context: As part of hospital policy, all children deemed high risk for the carriage of sickle cell disease presenting to the paediatric pre-operative assessment clinic at are to be tested for the condition. This involves well children undergoing a blood test. Problem: It was found that considerable parental/carer anxiety was produced by this testing and much time was spent in a busy clinic counselling parents about the condition and the need for testing. Through the production of an information leaflet explaining sickle cell disease and the reason behind testing children prior to an operation, it was hoped parents/carers would feel more informed and thus more willing for their children to testing. Assessment of problem and analysis of its causes: Prior to implementation of the leaflet, of 21 parents/carers only two thirds (14) felt they fully understood the reason for testing (5/5 on qualitative scale) and only two thirds (14) felt fully happy for their child to have the blood test (5/5). 71% of parents/carers (15) thought an information leaflet would be useful. Intervention: An information leafter was written by the authors, with expert review from a consultant paediatric haematologist. This passed the local procedure for patient information and was introduced to the clinic. Nursing staff handed out the leaflet to parents of children from at-risk ethnicities on arrival, giving parents time to read it before their consultation with the doctor. Study design: Over four weeks all parents/carers of children requiring sickle cell screening presenting to the clinic completed a qualitative questionnaire about their attitude to screening. An information leaflet was subsequently designed aimed at improving parent/carer's knowledge about sickle cell disease prior to consenting for the test. Following implementation of the leaflet a repeat qualitative questionnaire was carried out to assess the leaflet's impact. Strategy for change: Collaboration and education with nursing staff played a vital role in integrating the leaflet into the standard practice of the clinic. Measurement of improvement: A repeat questionnaire was carried out after introduction of the leaflet. Unfortunately there were relatively few children requiring screening during this month (total 9). Of those screened, 100% of parents felt that the reason for testing was completely clear (5/5 on quantitive scale). 89% were fully willing for their child to have the blood test. 89% reported that they found the leaflet useful. Effects of changes: Subjectively, we have found that the consultations with parents are quicker and easier due to reduced parental anxiety. Lessons learnt: Patient informaiton leaflets are a useful method of improving communication with families and improving families' experience of the service in pre-operative assessment. Message for others: This was a small project but was successful and we hope that our experience will encourage others to develop patient information when screening policies are in place as this is an area where medical concerns may not line up with parents' concerns.